Potensi Timah Primer Daerah Nyelanding Berdasarkan Analisis Data Geomagnet - Nandito Andrian; Mardiah Mardiah; Irvani Irvani (Universitas Negeri Gorontalo, 2020)
The village area of Nyelanding is estimated that there are still many regions that have primary tin prospects, this is confirmed by the large number of community mines that are still operating. This research purposes to see the distribution of primary tin mineralization and zones where deposition of tin. This research uses a geomagnetic exploration survey method with back – rover (mobile) system, the length of the track of ±3.5 km. The spacing of 200 m as many as 44 tracks, the direction of the track from south to north with data collection techniques starting from west to east. The data obtained of a magnetic strength value which will then be interpreted into a magnetic anomaly map to determine the location of recommendations. The research method used the Geomagnetic Survey method, of GSM-19 T Magnetometer. The interpretation results, the final map with the lowest magnetic anomaly shows magnetic anomaly values ranging from -7.2 to -3.3 nT at locations 1, 2, 3, the highest magnetic anomaly ranges from -4.6 to 5.0 nT in the southern part which is an area close to community settlements and the village highway of Nyelanding, and the direction of mineral distribution for zone 1 starts from east-west, zone 2 focuses towards the middle which means from southwest-northeast direction or vice versa, zone 3 from southwest-northeast. The upward continuity map 250 and matching the location of samples containing Sn levels around the recommended zone, it is certain that the area has cassiterite minerals in the zone namely zone 1 = (342.760 m2), zone 2 = (4001.770 m2), zone 3 = (372.876 m2).